Scalable fabrication of silicon nanotubes and their application to energy storage - Yoo, Jung-Keun (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.